Multiservice Loss Models for Broadband Telecommunication Networks - Ross, Keith W. (Springer London, 1995)
Loss networks ensure that sufficient resources are available when a call arrives. However, traditional loss network models for telephone networks cannot cope with today's heterogeneous demands, the central attribute of Asynchronous Transfer Mode (ATM) networks. This requires multiservice loss models. This publication presents mathematical tools for the analysis, optimization and design of multiservice loss networks. These tools are relevant to modern broadband networks, including ATM networks. Addressed are networks with both fixed and alternative routing, and with discrete and continuous bandwidth requirements. Multiservice interconnection networks for switches and contiguous slot assignment for synchronous transfer mode are also presented
Keywords: Engineering; Communications Engineering, Networks; Software Engineering/Programming and Operating Systems; Appl.Mathematics/Computational Methods of Engineering; Electronics and Microelectronics, Instrumentation; Software engineering; Applied mathematics; Engineering mathematics; Electronics; Microelectronics; Electrical engineering; ATM; Paketvermittlungsnetz; Breitbandkommunikation